Low rectus femoris mass index is closely associated with diabetic peripheral neuropathy - Wang, Lina; Lin, Xiaopu; Huang, Haishan; Wang, Yanfang; Liang, Xinxin; Zheng, Xiaobin; Xu, Lingling (Frontiers in Endocrinology, 2023)
Abstract Aims: To assess the association of rectus femoris mass index (RFMI) with diabetic peripheral neuropathy (DPN) in individuals with type 2 diabetes mellitus (T2DM). Methods: Totally 948 T2DM cases were enrolled. Nerve conduction parameters, quantitative sensory threshold and rectus femoris cross-sectional area (RFCSA) were obtained, and rectus femoris mass index (RFMI=RFCSA/height2) was derived. The patients were assigned to four groups based on interquartile spacing of RFMI. Results: Motor/sensory nerve amplitude and conduction velocity (CV) were signiﬁcantly lower in the low-level RFMI groups (all P<0.05). RFMI was positively associated with mean motor/sensory nerve amplitude and CV (both P<0.05). T2DM duration above 10 years and RFMI below 2.37cm²/m² had significant associations with DPN (both P<0.001). Receiver operating characteristic (ROC) curve analysis demonstrated cutoffs for T2DM duration and RFMI of 7 years and 2.2 cm²/m², respectively (AUC=0.75, 95% CI: 0.72-0.79; sensitivity, 68.4%; specificity, 66.8%). Conclusions: DPN is significantly associated with reduced RFMI in T2DM patients. Decreased muscle mass seems to be associated with motor/sensory nerve amplitude and CV. RFMI combined with T2DM duration may represent a potent tool for predicting DPN occurrence in T2DM cases. Keywords: diabetic peripheral neuropathy, sarcopenia, rectus femoris cross-sectional area, rectus femoris mass index, ultrasound